The chips are down: The influence of family on children's trust formation - Corrado Giulietti; Enrico Rettore; Sara Tonini (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Understanding the formation of trust at the individual level is a key issue given the impact that it has been recognized to have on economic development. Theoretical work highlights the role of the transmission of values such as trust from parents to their children. Attempts to empirically measure the strength of this transmission relied so far on the cross-sectional regression of the trust of children on the contemporaneous trust of their parents. We introduce a new identification strategy which hinges on a panel of parents and their children drawn from the German Socio-Economic Panel. Our results show that: 1) a half to two thirds of the observed variability of trust is pure noise irrelevant to the ransmission process; 2)this noise strongly biases the parameter estimates of the OLS regression of children's trust on parents' trust; however an instrumental variable procedure straightforwardly emerges from the analysis; 3) the dynamics of the component of trust relevant to the transmission process shed light on the structural interpretation of the parameters of this regression; 4) the strength of the flow of trust that parents pass to their children as well as of the sibling correlations due to other factors are easily summarized by the conventional R2 of a latent equation. In our sample, approximately one fourth of the variability of children's trust is inherited from their parents while two thirds are attributable to the residual sibling correlation.
Keywords: J62; P16; Z1; 330; Trust; Intergenerational transmission; Siblings correlations; Cultural transmission